Electronic press and its role in fighting against the Extremist ideology from the perspective of students of the Faculty of Arts at University of Jordan - Tahat, Othman (Opción)
This study aimed to investigate the role of the electronic media in facing the Extremist ideology from the perspective of students of the Faculty of Arts at University of Jordan. The study was conducted during the first term of the academic year 2019-2020, the study sample consisted of 450 undergraduate students who were elected by intentional sampling. In order to achieve the goals of the study, a questionnaire consisting of 12 items was developed to measuring the role of electronic media in fighting against Extremist ideology from the perspective of students of the Faculty of Arts at University of Jordan. Its authenticity was verified by presenting it to a committee of judges, the reliability was confirmed by using the method of internal consistency according to the equation of Cronbach’s Alpha and the value of reliability coefficient was 0.81.